2010
DOI: 10.1007/s13199-010-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of plant microbial symbionts: a review and meta-analysis

Abstract: In nature, plants often associate with multiple symbionts concurrently, yet the effects of tripartite symbioses are not well understood. We expected synergistic growth responses from plants associating with functionally distinct symbionts. In contrast, symbionts providing similar benefits to a host may reduce host plant growth. We reviewed studies investigating the effect of multiple interactions on host plant performance. Additionally, we conducted a meta-analysis on the studies that performed controlled mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 43 publications
11
94
2
Order By: Relevance
“…These results indicate that A. canescens is highly dependent upon both AMF and rhizobium colonization, regardless of nutrient availability. In contrast to the results of our previous meta-analysis, which mainly included annual agricultural plant species (Larimer et al 2010), we found the simultaneous effects of AMF and rhizobia on plant growth to be synergistic. The contrasting outcomes from these two studies may result from variation in dependency on belowground interactions between plants with different life history strategies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results indicate that A. canescens is highly dependent upon both AMF and rhizobium colonization, regardless of nutrient availability. In contrast to the results of our previous meta-analysis, which mainly included annual agricultural plant species (Larimer et al 2010), we found the simultaneous effects of AMF and rhizobia on plant growth to be synergistic. The contrasting outcomes from these two studies may result from variation in dependency on belowground interactions between plants with different life history strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…Because of the differences in growth strategies, short-lived plants typically have decreased investment in microbial partners and are often less responsive and less dependent upon soil microbes for success (Wilson andHartnett 1998, Middleton and. The outcome of simultaneous interactions with AMF and rhizobia in annual plants may be more sensitive to environmental conditions, such as nutrient environment and mutualistic effectiveness of the symbionts, allowing for the range of interactive effects seen in our previous meta-analysis, which was dominated by annual agricultural species (Larimer et al 2010). Studies investigating the interaction between nutritional symbionts of legume tree species have found plant responses similar to our results (Sprent and Parsons 2000, Tian et al 2002, Oliveira et al 2005.…”
Section: Influence Of Plant Life Historysupporting
confidence: 84%
See 1 more Smart Citation
“…However the interactive effects of AM fungi and N 2 -fixing organisms are not necessarily positive for planthost growth. Larimer et al (2010) and Kaschuk et al (2010) conducted meta-analyses on the available literature and noted an absence of further plant-host responses when plants were simultaneously colonized with AM fungi and either rhizobia or free-living N 2 -fixers, despite the fact that responses to separate inoculation with either AM fungi or N 2 -fixers were positive. With regards to qualitative shifts in the nitrogen fixers-community, Welsch et al (2010) manipulated the AM community through the addition of benomyl in the rhizosphere of Spartina patens and recorded nifH gene community differences that were maximized at the vegetative point of S. patens growth.…”
Section: N 2 -Fixationmentioning
confidence: 99%
“…In contrast, R. pseudoacacia formed nodules with nitrogen fixing bacteria in the native soil. The interactions between nonmycorrhizal fungal endophytes and the AM fungi are known to enhance plant invasiveness (Larimer et al, 2010). Bacterial endophytes help invasive plants by providing a higher amount of phosphorous and iron and also secretes plant growth promoting hormones (IAA), thus increasing the competitive ability of the invasive plants (Rout et al, 2013).…”
Section: Interactions Between Soil Biota and Invasive Plantsmentioning
confidence: 99%